Evaluation of Undergraduates and Postgraduates' Utilisation of Internet for Academic Purpose in STREAM Fields - Badmus, Olalekan; Jita, Thuthukile; Jita, Loyiso C. (Universitas Terbuka, 2023)
This study examines undergraduates and postgraduates use of the internet for academic purposes in STREAM fields. A mixed method research which sampled 100 respondents selected through snowballing sampling technique. Four research questions and one hypothesis guided this study. Two instruments namely Internet Usage Questionnaire (IUQ) and semi-structured interview on challenges experienced in the utilisation of internet (IUIT) were employed for data collection. Standard deviation and independent sample t-test analysed the descriptive (quantitative) aspect of questions and hypothesis raised respectively, while thematic analysis was employed in the narrative (qualitative) section. The study found that mobile apps, software, and website were among the media through which students access academic resources on the internet.Â No significant difference was found in the level of usage of the internet for academic purposes between undergraduates and postgraduates in STREAM fields. Poor internet facility, high cost of internet subscription, wide search for relevant academic resources due to inaccessibility to paid resources and many ad pop-ups owing to unlicensed software were among the challenges experienced by the respondents. Furthermore, stakeholders are enjoined to make available fast and affordable internet to ease the concerns raised.